Complex estimation of functional changes in the organism of healthy rats which consumed water of the lake Kagul as drinking water - Kovalchuk L.I.; Mokiyenko A.V.; Nasibullin B.A.; Solodova L.B.; Guscha S.G.; Oleshko O.Ya.; Bakholdina O.I. (Medičnì Perspektivi)
In the work results of a complex estimation of functional changes in an organism of healthy rats which consumed water of the lake of Kagul as drinking water are given. Conformity of water of the lake of Kagul to requirements of operating standard documents except for nitrogen ammonia, nitrogen nitrit and the general organic carbon is established. 3 kinds of cyanobacteriaе, in particular high levels of Aphanocapsa pulverea, which causes water "flowering" are revealed. It is shown that the use of water of the lake of Kagul as drinking, causes strengthening of activity of central nervous system in healthy rats; some increase of possibilities of organism sensitisation development and specific phagocytosis, certain displays of disbalance of hummoral component of the immune response and expansion of autoimmune processes in the organism. In the view of absence of hyginicaly significant concentration of anthropogenous pollutants, the idea that the revealed biological effects are a consequence of cyanotoxins action produced by revealed cyanobacteriaе is presented. Necessity of expansion and continuation of researches on cyanobacteriaе in the context of their revealing in water, their identifications, influences of these xenobiotics on condition of warm-blooded animals and the human is proved.